Literatura polska w Chinach i wymiana kulturalna między Polską a Chinami. Zapiski tłumacza - Zhenhui, Zhang (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article is an introduction into the presence of Polish literature in China from the perspective of one of its most active researchers and translators. The author describes his fascination with Bolesław Prus’s work that resulted in the Chinese translation of Lalka (The Doll) and his work on two-volume Historia literatury polskiej (The history of Polish literature) aimed at Chinese readers.